Retraction Note: Upregulation of the long non-coding RNA AFAP1-AS1 affects the proliferation, invasion and survival of tongue squamous cell carcinoma via the Wnt/β-catenin signaling pathway - Ze-you Wang; Min Hu; Min-hui Dai; Jing Xiong; Shuai Zhang; Han-jiang Wu; Shan-shan Zhang; Zhao-jian Gong (Molecular Cancer, 2019)
The authors have retracted this article [1] because there are errors in Figures 4a and 4b